2014
DOI: 10.1111/aos.12609
|View full text |Cite
|
Sign up to set email alerts
|

Retinal fluorescence lifetime imaging ophthalmoscopy measures depend on the severity of Alzheimer's disease

Abstract: ABSTRACT.Purpose: To determine alterations in the retina of patients with Alzheimer's disease (AD) by the newly developed technique of fluorescence lifetime imaging ophthalmoscopy (FLIO) in a pilot study. Methods: FLIO set-up uses a scanning laser ophthalmoscope (HRA2, Heidelberg Engineering, Germany), which was modified by the use of an excitation pulse laser BLD440 (Becker&Hickl, Berlin, Germany) and detection of fluorescence lifetime by time-correlated single photon counting (TCSPC; Becker&Hickl) in two spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 40 publications
3
63
0
Order By: Relevance
“…Nearly a century following the first description of these signs in the brain, documentation of their manifestation in ocular tissues has begun to emerge [1, 69, 91, 100, 107, 113, 163, 178]. Table 1 presents key findings from research on hallmark AD pathology in the ocular tissues of human patients.…”
Section: Hallmark Pathology In Ocular Tissues Of Ad Patientsmentioning
confidence: 99%
“…Nearly a century following the first description of these signs in the brain, documentation of their manifestation in ocular tissues has begun to emerge [1, 69, 91, 100, 107, 113, 163, 178]. Table 1 presents key findings from research on hallmark AD pathology in the ocular tissues of human patients.…”
Section: Hallmark Pathology In Ocular Tissues Of Ad Patientsmentioning
confidence: 99%
“…Another new technique called fluorescence lifetime imaging ophthalmoscopy (FLIO) has been developed which demonstrates changes in the retina of patients of AD. It uses a scanning laser ophthalmoscope coupled to an excitation pulse laser BLD 440 and detects fluorescence lifetime (Jentsch et al 2015). It measures fluorescence lifetime by measuring time correlated single photon counting in two spectral channels.…”
Section: Fluorescent Ligand Eye Scanning System (Fles)mentioning
confidence: 99%
“…There were reports demonstrating a decrease in the thickness of RNFL in AD patients [5,70,71,72,73,74,75,76], while other studies found no differences in the RNFL thickness of AD patients [77,78]. These inconsistent results might be due to the distinct evaluation techniques, as well as the evaluation criteria, such as the retinal region [73].…”
Section: Retinal Alterations In Admentioning
confidence: 99%
“…A recent study showed that changes in RNFL might be dependent on the progression of the pathology [79]. With the evaluation of RNFL being performed with spectral OCT, a noninvasive and cost-effective technique that allows the quantification of retinal layer thickness, it is reasonable to hypothesize that a reduction in RNFL thickness may be used as an early biomarker for AD [65,74,75]. …”
Section: Retinal Alterations In Admentioning
confidence: 99%